Comment on "Productivity Is a Poor Predictor of Plant Species Richness" - Luca Borger (Science, 2012)
Adler et al. (Reports, 23 September 2011, p. 1750) reported “ weak and variable” relationships between productivity and species richness and dispute the “ humped-back” model (HBM) of plant diversity. We show that their analysis lacks sufficient high-productivity sites, ignores litter, and excludes anthropogenic sites. If corrected, the data set of Adler et al. would apparently yield strong HBM support.